2020
DOI: 10.1186/s12891-020-03382-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of treatment with a non-invasive foot worn biomechanical device on subjective and objective measures in patients with knee osteoarthritis- a retrospective analysis on a UK population

Abstract: Background: Osteoarthritis is a major cause of pain and disability worldwide, therefore ways of treating this condition are paramount to a successful health system. The purpose of the study was to investigate the changes in spatial-temporal gait parameters and clinical measurements following treatment with a non-invasive foot-worn biomechanical device on patients with knee osteoarthritis within the UK. Methods: A retrospective analysis was carried out on 455 patients with knee osteoarthritis. All patients were… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…22 Therefore, any intervention that helps reduce the number of procedures will directly affect the economic burden, as most of the direct costs of knee OA are associated with surgery. Specifically, previous studies suggest that patients that were treated with this intervention reported a significant reduction in pain and improvement in function and quality of life 13,[23][24][25][26] due to changes in gait biomechanics, specifically, a reduction in knee frontal and sagittal moments 14,27 and better neuromuscular control and synchronized muscle activation patterns. 20 With the lack of effective noninvasive therapeutic options for patients with knee OA, clinicians prescribe pain relief medication in the hope of relieving patients' symptoms, often underestimating their potentially harmful consequences.…”
Section: Discussionmentioning
confidence: 99%
“…22 Therefore, any intervention that helps reduce the number of procedures will directly affect the economic burden, as most of the direct costs of knee OA are associated with surgery. Specifically, previous studies suggest that patients that were treated with this intervention reported a significant reduction in pain and improvement in function and quality of life 13,[23][24][25][26] due to changes in gait biomechanics, specifically, a reduction in knee frontal and sagittal moments 14,27 and better neuromuscular control and synchronized muscle activation patterns. 20 With the lack of effective noninvasive therapeutic options for patients with knee OA, clinicians prescribe pain relief medication in the hope of relieving patients' symptoms, often underestimating their potentially harmful consequences.…”
Section: Discussionmentioning
confidence: 99%
“…A home-based biomechanical intervention (AposHealth ® , New York, US) that includes a unique foot-worn device to manipulate the center of pressure (COP) and train neuromuscular control and a home-based treatment plan has been in use for a few years. The therapy addresses the underlying biomechanical aspects of knee OA (Haim et al Solomonow-Avnon, Herman, and Wolf 2019;Khoury-Mireb et al 2019;Debbi, Wolf, and Haim 2012;Goryachev, Debbi, Haim, Rozen, et al 2011) (i.e., reducing loads by shifting the center of pressure and neuromuscular training), while reducing pain and improving function (Goryachev, Debbi, Haim, Rozen, et al 2011;Debbi et al 2015;Haim et al 2012;Bar-Ziv et al 2010Drexler et al 2012;Lador et al 2013;Elbaz et al 2010Elbaz et al , 2011Lubovsky et al 2015;Herman et al 2018;Reichenbach et al 2020;Miles and Greene 2020;Barzilay et al 2015;Elbaz et al 2009;Lee et al 2018;Elbaz et al 2013;Haim et al 2013;Atoun et al 2016;Elbaz, Debbi, et al 2014;Yaari et al 2015;Debbi et al 2019;Solomonow-Avnon et al 2017;Segal et al 2013;Tenenbaum et al 2017) (Figure 2). Patients are instructed to wear a personally calibrated device for 30-60 minutes a day while performing their daily activities at home or work (usage time may increase gradually, depending on progress and symptoms).…”
Section: Biomechanical Alteration Of Gait (Bmag)mentioning
confidence: 99%
“…Clinically, there is growing evidence on the effectiveness of this therapy in several MSK conditions, including knee OA, (Goryachev, Debbi, Haim, Rozen, et al 2011;Debbi et al 2015;Haim et al 2012;Bar-Ziv et al 2010Drexler et al 2012;Lador et al 2013;Elbaz et al 2010Elbaz et al , 2011Lubovsky et al 2015;Herman et al 2018;Reichenbach et al 2020;Miles and Greene 2020) low back pain (Barzilay et al 2015;Elbaz et al 2009;Lee et al 2018), degenerative meniscal tear (Elbaz et al 2013) anterior knee pain (Haim et al 2013) spontaneous osteonecrosis of the knee (Atoun et al 2016), total knee arthroplasty (Elbaz, Debbi, et al 2014;Yaari et al 2015;Debbi et al 2019), hip OA, (Drexler et al 2013;Solomonow-Avnon et al 2017), total hip arthroplasty (Segal et al 2013), and recurrent ankle sprain (Tenenbaum et al 2017). In summary, patients report a significant reduction in pain and improved function and quality of life.…”
Section: Biomechanical Alteration Of Gait (Bmag)mentioning
confidence: 99%